Entropy Stabilization Strategy for Enhancing the Local Structural Adaptability of Li‐Rich Cathode Materials. Issue 7 (20th December 2022) - Song, Jin; Ning, Fanghua; Zuo, Yuxuan; Li, Ang; Wang, Hangchao; Zhang, Kun; Yang, Tonghuan; Yang, Yali; Gao, Chuan; Xiao, Wukun; Jiang, Zewen; Chen, Tao; et al.
Abstract: Layered Li‐rich cathode materials with high reversible energy densities are becoming prevalent. However, owing to the activation of low‐potential redox couples and the progressively irreversible structural transformation caused by the local adjustment of transition‐metal ions in the intra/interlayer driven by anionic redox, continuous capacity degradation, and voltage decay emerge, thus greatly reducing the energy density and increasing the difficulty of battery system management. Herein, layered Li‐rich cathode materials with higher intralayer configuration entropy have more local structural diversity and higher distortion energy, resulting in superior local structural adaptability with no drastic redox couple evolution, major local structural adjustment, or obvious layered‐to‐spinel phase transition. Consequently, the energy retention of the entropy‐stabilization‐strategy‐enhanced Li‐rich cathode materials is almost twice that of a typical Li‐rich cathode material (Li1.20 Mn0.54 Ni0.13 Co0.13 O2, T‐LRM) after 3 months of cyclic testing. Moreover, when cycled at 1 C, the voltage degradation per cycle is less than 0.02%, that is, it results in a voltage loss of only 0.8 mV per cycle, which is excellent performance. This study paves the way for the development of Li‐rich cathode materials with stabilized intralayer atomic arrangements and high local structural adaptability. Abstract : Layered Li‐rich cathode materials with higher intralayer configuration entropy have more local structural diversity and higher distortion energy, resulting in superior local structural adaptability: no drastic redox couple evolution, major local structural adjustment, or obvious layered‐to‐spinel phase transition. This leads to high stability of the capacity and voltage, greatly enhancing energy retention.